Thermodynamic analysis and comparison of four insulation schemes for liquid hydrogen storage tank. (15th April 2019) - Zheng, Jianpeng; Chen, Liubiao; Wang, Jue; Xi, Xiaotong; Zhu, Honglai; Zhou, Yuan; Wang, Junjie
Highlights: A novel model of composite insulation system (SOFI, MLI, VDMLI and VCS) for LH2 tank. Heat reduction of VDMLI + VCS is 83.12% than MLI and 66.32% than VDMLI. VDMLI and VCS are of mutual promotion with improvement greater than their simple sum. With vacuum changing, influence of VCS on composite insulation system is analyzed. Abstract: Hydrogen has more energy per unit mass (141.8 MJ/kg) than any other fuel but also has the lowest gaseous density (0.084 kg/m 3 ), and liquid hydrogen (LH2 ) storage is a solution with high energy density. However, LH2 storage has the characteristics of low temperature (20 K) and easy evaporation, putting forward higher requirements for insulation system. At present, the improvement and optimization of insulation system consisting of spray on foam insulation (SOFI), multilayer insulation (MLI) and variable density MLI (VDMLI) is a hot topic. Considering the considerable sensible heat of hydrogen, this paper introduces self-evaporation vapor cooled shield (VCS) into the above-mentioned insulation systems to fully recover its sensible heat to improve insulation performance. A thermodynamic model has been established to study the insulation properties of composite insulation system for LH2 tank, and the results have good agreement with test data. Coupling effects among them are analyzed and the optimization strategies of MLI, VDMLI and VCS are quantitatively explained to obtain better insulation performance. The heat flux and temperature profile of four insulation structures (MLI, VDMLI, MLI + VCS and VDMLI + VCS) have also been quantitatively analyzed, which can provide guidance for insulation system optimization. The insulation performance of composite insulation system under different vacuum conditions have also been compared.